Bioinformatics and system biology approach to identify the influences of SARS-CoV-2 on metabolic unhealthy obese patients - Huang, Tengda; Jiang, Nan; Song, Yujia; Pan, Hongyuan; Du, Ao; Yu, Bingxuan; Li, Xiaoquan; He, Jinyi; Yuan, Kefei; Wang, Zhen (Frontiers in Molecular Biosciences, 2023)
The severe acute respiratory syndrome coronavirus 2 (SARS-COV-2) has posed a significant challenge to individuals' health. Increasing evidence shows that patients with metabolic unhealthy obesity (MUO) and COVID-19 have severer complications and higher mortality rate. However, the molecular mechanisms underlying the association between MUO and COVID-19 are poorly understood.We sought to reveal the relationship between MUO and COVID-19 using bioinformatics and systems biology analysis approaches. Here, two datasets (GSE196822 and GSE152991) were employed to extract differentially expressed genes (DEGs) to identify common hub genes, shared pathways, transcriptional regulatory networks, gene-disease relationship and candidate drugs.Results: Based on the identified 65 common DEGs, the complement-related pathways and neutrophil degranulation-related functions are founded to be mainly affected. The hub genes, which included SPI1, CD163, C1QB, SIGLEC1, C1QA, ITGAM, CD14, FCGR1A, VSIG4 and C1QC, were identified. From the interaction network analysis, 65 transcription factors (TFs) were found to be the regulatory signals. Some infections, inflammation and liver diseases were found to be most coordinated with the hub genes. Importantly, Paricalcitol, 3,3',4,4',5-Pentachlorobiphenyl, PD 98059, Medroxyprogesterone acetate, Dexamethasone and Tretinoin HL60 UP have shown possibility as therapeutic agents against COVID-19 and MUO.This study provides new clues and references to treat both COVID-19 and MUO.